Plan Municipal de Gestión del Riesgo de Desastre (2021)
The municipal mayor of Paime Cundinamarca aims to update the Municipal Disaster Risk Management Plan to evaluate the risk scenarios that occur in the different lands of the municipality, this in order to carry out processes for their mitigation. When an emergency occurs, the municipality has its respective disaster risk management office, with the purpose of evaluating all the risk scenarios presented either by floods, forest fires, mass movements and geological failure